Pengaruh Proses Rekrutmen Dan Seleksi Terhadap Kinerja Karyawan Pada PT. Thamrin Brothers Kaur - M. Ramandika Okta; Neri Susanti; Abdul Rahman (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
In the current era of globalization, companies are required to be able to compete with other companies. Currently the human resource element is considered very important for the company. The succes of an organization in achieving its goals is strongly influeced by the performance of its employess. The purpose of this study was to determine the effect of the recruitment and selection process on employee performance at PT. Thamrin Brothers Kaur. The sample in this study were 32 employees of PT. Thamrin Brothers Kaur. Sampling method by census. Data collection techniques using a questionnaire. The analytical method used is multiple regression analysis, determination test, hypothesis test t and f, classic assumption test. The result of the regression equation are Y = 5.529 + 0.319X1 + 0.631X2 meaning that the recruitment and selection process has a positive and significant influence on employee performance at PT. Thamrin Brothers Kaur. This illustrates that if the recruitment and selection variables increase, employee performance will also increase.